2021
DOI: 10.14309/ajg.0000000000001192
|View full text |Cite|
|
Sign up to set email alerts
|

Combined Use of Aspirin and Selective Serotonin Reuptake Inhibitors Is Associated With Lower Risk of Colorectal Cancer: A Nested Case-Control Study

Abstract: INTRODUCTION: Chemoprevention against colorectal cancer (CRC) is greatly needed. As the development of CRC involves multiple dysfunctional pathways, it is thus reasonable to combine some agents that address several pathways to achieve better chemoprotection. We aimed to explore whether the use of aspirin and selective serotonin reuptake inhibitors (SSRIs)—either as monotherapy or combined—can have a clinical benefit against CRC. METHODS: We performed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Several epidemiological and clinical studies supported the potential benefits of NSAIDs in the prevention and treatment of several cancers, including colon, ,, ovarian, breast, , lung, and prostate . In this context, long-term use of aspirin reduces the risk of colorectal, , ovarian, , breast, and prostate cancer and hepatocellular carcinoma. , Further, almost 90 clinical trials involving aspirin are being or have been carried out, such as the randomized phase II trial that demonstrated aspirin’s pharmacological efficacy in preventing colorectal cancer in patients at increased risk of colorectal cancer . Thus, the U.S. Preventive Services Task Force (USPSTF) recommended that aspirin can be used to help reduce the risk of cancers including colorectal cancer, although the long-term use of aspirin in older individuals is still being discussed , and needs further confirmation.…”
Section: Cancer Prevention and Treatmentmentioning
confidence: 99%
“…Several epidemiological and clinical studies supported the potential benefits of NSAIDs in the prevention and treatment of several cancers, including colon, ,, ovarian, breast, , lung, and prostate . In this context, long-term use of aspirin reduces the risk of colorectal, , ovarian, , breast, and prostate cancer and hepatocellular carcinoma. , Further, almost 90 clinical trials involving aspirin are being or have been carried out, such as the randomized phase II trial that demonstrated aspirin’s pharmacological efficacy in preventing colorectal cancer in patients at increased risk of colorectal cancer . Thus, the U.S. Preventive Services Task Force (USPSTF) recommended that aspirin can be used to help reduce the risk of cancers including colorectal cancer, although the long-term use of aspirin in older individuals is still being discussed , and needs further confirmation.…”
Section: Cancer Prevention and Treatmentmentioning
confidence: 99%
“…Accumulating epidemiological studies reveal that SSRIs use has a lower risk of death from various cancer types, such as liver cancer, bladder cancer, kidney cancer, breast cancer, endometrial cancer, and ovarian cancer [6][7][8][9][10][11] . Recently, our group also showed that SSRIs monotherapy was inversely associated with colorectal cancer risk, and the combined use of aspirin and SSRIs showed a synergistic effect 12 . Consistent with clinical observations, data from in vitro cell experiments and preclinical models suggest that SSRIs exert substantial anti-tumor effects, including but not limited to cell senescence, cell apoptosis, invasive potential, and drug resistance [13][14][15][16] .…”
Section: Introductionmentioning
confidence: 98%
“…In another study, however, high doses of sertraline did not improve mood symptoms, wellbeing, or survival of patients with advanced-stage cancer but without major depression [ 19 ]. Notably, several epidemiological studies have shown that chronic use of SSRIs can lower the risk of developing some types of cancer [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%